Copanlisib plus rituximab versus placebo plus rituximab in patients with relapsed indolent non-Hodgkin lymphoma (CHRONOS-3): a double-blind, randomised, placebo-controlled, phase 3 trial. Issue 5 (May 2021) - Matasar, Matthew J; Capra, Marcelo; Özcan, Muhit; Lv, Fangfang; Li, Wei; Yañez, Eduardo; Sapunarova, Katya; Lin, Tongyu; Jin, Jie; Jurczak, Wojciech; Hamed, Aryan; Wang, Ming-Chung; et al.
Summary: Background: Copanlisib, an intravenous pan-class I PI3K inhibitor, showed efficacy and safety as monotherapy in patients with relapsed or refractory indolent non-Hodgkin lymphoma who had received at least two therapies. The CHRONOS-3 study aimed to assess the efficacy and safety of copanlisib plus rituximab in patients with relapsed indolent non-Hodgkin lymphoma. Methods: CHRONOS-3 was a multicentre, double-blind, randomised, placebo-controlled, phase 3 study in 186 academic medical centres across Asia, Australia, Europe, New Zealand, North America, Russia, South Africa, and South America. Patients aged 18 years and older with an Eastern Cooperative Oncology Group performance status of no more than 2 and histologically confirmed CD20-positive indolent B-cell lymphoma relapsed after the last anti-CD20 monoclonal antibody-containing therapy and progression-free and treatment-free for at least 12 months, or at least 6 months for patients unwilling or unfit to receive chemotherapy, were randomly assigned (2:1) with an interactive voice-web response system via block randomisation (block size of six) to copanlisib (60 mg given as a 1-h intravenous infusion on an intermittent schedule on days 1, 8, and 15 [28-day cycle]) plus rituximab (375 mg/m 2 given intravenously weekly on days 1, 8, 15, and 22 during cycle 1 and day 1 of cycles 3, 5, 7, and 9) or placebo plus rituximab, stratified on the basis of histology, progression-free and treatment-free interval, presence of bulky disease, and previous treatment with PI3K inhibitors. The primary outcome was progression-free survival in the full analysis set (all randomised patients) by masked central review. Safety was assessed in all patients who received at least one dose of any study drug. This study is registered with ClinicalTrials.gov, NCT02367040 and is ongoing. Findings: Between Aug 3, 2015, and Dec 17, 2019, 652 patients were screened for eligibility. 307 of 458 patients were randomly assigned to copanlisib plus rituximab and 151 patients were randomly assigned to placebo plus rituximab. With a median follow-up of 19·2 months (IQR 7·4–28·8) and 205 total events, copanlisib plus rituximab showed a statistically and clinically significant improvement in progression-free survival versus placebo plus rituximab; median progression-free survival 21·5 months (95% CI 17·8–33·0) versus 13·8 months (10·2–17·5; hazard ratio 0·52 [95% CI 0·39–0·69]; p<0·0001). The most common grade 3–4 adverse events were hyperglycaemia (173 [56%] of 307 patients in the copanlisib plus rituximab group vs 12 [8%] of 146 in the placebo plus rituximab group) and hypertension (122 [40%] vs 13 [9%]). Serious treatment-emergent adverse events were reported in 145 (47%) of 307 patients receiving copanlisib plus rituximab and 27 (18%) of 146 patients receiving placebo plus rituximab. One (<1%) drug-related death (pneumonitis) occurred in the copanlisib plus rituximab group and none occurred in the placebo plus rituximab group. Interpretation: Copanlisib plus rituximab improved progression-free survival in patients with relapsed indolent non-Hodgkin lymphoma compared with placebo plus rituximab. To our knowledge, copanlisib is the first PI3K inhibitor to be safely combined with rituximab and the first to show broad and superior efficacy in combination with rituximab in patients with relapsed indolent non-Hodgkin lymphoma. Funding: Bayer.